2021
DOI: 10.1007/s11627-021-10234-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation, lactucin quantification, and antibacterial activity of Indian lettuce (Lactuca indica L.)

Abstract: Lactuca indica L. (Asteraceae), a wild lettuce, is used as a vegetable and in traditional medicine. This study aims to establish in vitro propagation protocol and evaluate lactucin and antibacterial property from in vitro and natural plant tissues. Leaf blades and petioles were cultured in vitro on Murashige and Skoog (MS) medium supplemented with various concentrations of 6-benzylaminopurine (BAP) and 1.2 mg L–1 indoleacetic acid (IAA). Leaf petioles and a lower BAP concentration (0.5 mg L–1) were optimal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…(Asteraceae) 18 and Cichorium intybus L. 19 and exhibited various biological activities. Some compounds are commercially available as drug formulations, such as artemisinin, an antimalarial drug [20][21] , which has been reported to exhibit antibacterial activities 22 . Previous studies reported that diverse sesquiterpenoids are present in the crude extract, which may possess antibacterial activity due to the presence of lactucin 23-27 .…”
Section: Discussionmentioning
confidence: 99%
“…(Asteraceae) 18 and Cichorium intybus L. 19 and exhibited various biological activities. Some compounds are commercially available as drug formulations, such as artemisinin, an antimalarial drug [20][21] , which has been reported to exhibit antibacterial activities 22 . Previous studies reported that diverse sesquiterpenoids are present in the crude extract, which may possess antibacterial activity due to the presence of lactucin 23-27 .…”
Section: Discussionmentioning
confidence: 99%
“…They further established a direct correlation between the antimicrobial effectiveness of L. indica and the quantity of lactucin present in the plant. 11 In 2011, Edziri HA and collaborators documented the antimicrobial 12 In 2007, KIM IH and colleagues documented the antimicrobial properties of U. lactuca. The author noted potent activity specifically targeting the bacterium methicillinresistant Staphylococcus aureus.…”
Section: Antibacterial Activitymentioning
confidence: 99%